Review and Development of a Scalable Lightweight Blockchain Integrated Model (LightBlock) for IoT Applications - Mahmoud M.A.; Gurunathan M.; Ramli R.; Babatunde K.A.; Faisal F.H. (MDPI, 2024)
The Internet of things (IoT) is on the rise, and it is increasingly becoming a ubiquitous computing service that requires large data storage and processing. Due to the limited capabilities of most IoT devices, they always rely on cloud services for storage and computing, posing security and privacy risks. Due to its significant aspects, such as data security and privacy, Blockchain (BC) has drawn significant interest in alleviating these concerns. Despite its potential benefits, Blockchains high complexity and limited scalability make it computationally expensive and incompatible with IoT devices requiring lightweight solutions. Although several models have been proposed for this purpose, the issue is still far from being resolved. These models have significant constraints, such as resource optimization during operation. By presenting a scalable lightweight Blockchain integrated model (LightBlock), the primary objective of this work is to enable the usage of BC in the IoT environment. LightBlock is implemented by optimizing the components of a lightweight, scalable Blockchain. Lastly, the studys findings should provide IoT users with a high level of security and privacy by ensuring applicability and offering end-to-end security. 2023 by the authors.